Pemberdayaan Wanita Di Desa Banjar Timur Gapura Sumenep Melalui Pelatihan Pembuatan Biskuit Ekstrak Daun Kelor Untuk Meminimalisir Resiko Balita Gizi Buruk - Zakiyah Yasin; Eka Meiri Kurniyati; Emdat Suprayitno (Jurnal Empathy Pengabdian Kepada Masyarakat, 2021)
Background: One indicator of the success of community welfare is poor nutrition. The impact of malnutrition is extensive on the governance structure, especially starting from the economy, intelligence, and quality, which affects children's future. Of course, to reduce poor nutritional status, the latest and modern breakthroughs are needed, one of which is using biscuits to fulfill additional food for toddlers. This is very interesting because toddlers tend to like snacks such as biscuits. The development of biscuit production is increasingly varied and diverse by adding other ingredients. One of them is the addition of moringa oleifera leaf extract, which improves children's nutrition. Methods: Oservational and analytical methods by Socialization, Training, and Mentoring. Results: Activity participants can understand and make Moringa leaf extract biscuits. Participants can also develop the effects of the training to provide health benefits for children and have economic value. Conclusion: empowering community groups (pokmas) in East Banjar village to develop moringa oleifera as a productive economy and healthy food for all communities, especially toddlers.